Synthesizing Electrodes Into Electrochemical Sensor Systems - Mourzina, Yulia G.; Ermolenko, Yuri E.; Offenhäusser, Andreas (Frontiers in Chemistry, 2021)
Electrochemical sensors that can determine single/multiple analytes remain a key challenge in miniaturized analytical systems and devices. In this study, we present in situ synthesis and modification of gold nanodendrite electrodes to create an electrochemical system for the analysis of hydrogen peroxide. The sensor system consisted of the reference and counter electrodes as well as the working electrode. Electrochemical reduction of graphene oxide, ErGO, on the thin-film gold and gold nanodendrite working electrodes was used to achieve an efficient sensor interface for the adsorption of a biomimetic electrocatalytic sensor material, Mn(III) meso-tetra(N-methyl-4-pyridyl) porphyrin complex, with as high as 10-10 mol cm-2 surface coverage. The sensor system demonstrated a detection limit of 0.3 µM H2O2 in the presence of oxygen. Electrochemical determination of hydrogen peroxide in plant material in the concentration range from 0.09 to 0.4 µmol (gFW)-1 using the electrochemical sensor system was shown as well as in vivo real-time monitoring of the hydrogen peroxide dynamics as a sign of abiotic stress (intense sunlight). Results of the electrochemical determination were in good agreement with the results of biochemical analysis with the spectrophotometric detection. We anticipate that this method can be extended for the synthesis and integration of multisensor arrays in analytical microsystems and devices for the quantification and real-time in vivo monitoring of other analytes and biomarkers.